Les visiteurs du soir [videorecording (DVD)] - Carné, Marcel; Arletty, 1898-1992; Déa, Marie; Ledoux, Fernand, 1897-1993; Cuny, Alain; Herrand, Marcel (Criterion collection, 2012)
A lyrical medieval fantasy from the French director Marcel Carne. Two strangers dressed as minstrels arrive at a castle in advance of court festivities, and it is revealed that they are actually emissaries of the devil himself, dispatched to spread heartbreak and suffering. Their plans, however, are thwarted by an unexpected intrusion: Human love. Often interpreted as an allegory for the Nazi occupation of France, during which it was made.